CRIMINAL RESPONSIBILITY OF ACTIVE ARMY MEMBERS IN BRIBERY CRIME IN GOODS AND S ERVICES PROJECT CASES AT THE NATIONAL SEARCH AND RESCUE AGENCY (BASARNAS) - Syahriza, M. (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
The Corruption Eradication Commission named the Head of Basarnas who is also a member of the Indonesian National Army as a suspect in the procurement of debris detection equipment for the 2021-2023 Fiscal Year. Corruption crimes committed by members of the military always attract attention, especially because of differences of opinion and legal conflicts related to the courts that have the authority to try special cases involving military subjects. The problems in this study are 1) How is the criminal liability of active military members in bribery cases in goods and services projects? 2) How is the enforcement of criminal law in corruption cases involving active military members through connectivity trials? The theories used are the theory of criminal responsibility and the theory of law enforcement. This research is categorized as normative legal research. Normative legal research is based on current laws and regulations. This study uses 3 (three) different approaches: legislation (statute approach), case approach and conceptual approach. The results of the study show that, First, criminal liability for active military members who commit corruption in the form of bribery, in this case Air Marshal Henri Alfiandi, is still considered a soldier even though he also holds a civilian position (Basarnas) in accordance with Article 47 Paragraph (2) of Law Number 34 of 2004 concerning the Indonesian National Army in conjunction with Law Number 3 of 2025, so that the provisions of military law remain attached and apply to him because according to the law he is not required to resign or retire from active military service. In terms of criminal liability based on Article 66 letter (c) of Law Number 31 of 1997 concerning Military Justice, it explains the settlement and implementation of prosecution of certain criminal cases whose procedures are specifically regulated by coordinating with the Attorney General's Office, Military Police and other law enforcement agencies. Second, enforcement of criminal law for perpetrators of corruption involving members of the Indonesian National Army and civilians who were tried separately. The civilians involved have been sentenced by the Corruption Court. Meanwhile, the 2 (two) perpetrators who are military members have not yet been sentenced by the Military Court. In handling joint connectivity cases with the Military Police, the KPK experienced obstacles/limitations. The KPK could only coordinate with the Military Police in the investigation stage and ended up splitting the case files. The KPK investigated civilian defendants and the Military Police investigated TNI members. The separation of the process of handling corruption crimes seemed to be increasingly protracted due to disharmony in laws and regulations.